Influences of physicochemical stresses on injury and inactivation behaviour of Listeria innocua - Miller, Fátima A. (2018)
Many minimally processed foods depend on a combination of inhibitory factors to reduce the hazard of foodborne illness. Therefore, inactivation of Listeria innocua was studied according to a 24 factorial experiment designed to draw conclusions about temperature (52.5 °C and 65.0 °C), pH (4.5 and 7.5), water activity (aw=0.95 and 0.99) and solute type (NaCl and glycerol) effects. Three different recovery media were used to assess injured cells. Survival data were fitted with a Gompertz-based model and kinetic parameters (shoulder, maximum inactivation rate – kmax, and tail) were estimated. Results showed that shoulder was affected by temperature, pH and combined effects; kmax was influenced by all factors and their combinations; and tail was affected by aw, temperature and aw/pH combination. Results demonstrated the potential occurrence of microbial cross-protection survival techniques between the various stresses, e.g. heat and osmolarity. Indeed, this work clearly established that, to avoid hazards, Listeria inactivation must be evaluated with a maximum of environmental factors that undergo alterations. Only thus, appropriate food preservation treatments can be developed and consequently, the safety of food products can be assured.